Machine Learning Optimization Using Calculus (Journal of Advances and Scholarly Researches in Allied Education, 2025)
Optimization of Machine Learning Through Calculus Abstract One significant field in the domain of Information Technologies is machine learning. This discipline is about the ability of the system to learn from data and perform intelligent operations. There are many tasks involved in the domain of machine learning; one of them is model optimization. Optimizing a machine learning model is the goal of this study. In particular, this work focuses on the role of calculus and derivatives in machine learning optimization. Moreover, gradient descent is regarded as a well-known technique for minimizing loss functions. This study focuses on theoretical analysis and practical examples. Results reveal that using calculus; it is easy to make machine learning models more precise.